EVALUASI KESESUAIAN WAKTU TUNGGU PELAYANAN RESEP DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT UMUM KABUPATEN TANGERANG NOVEMBER 2022 - Sabrina, Alifa; Rianto, Leonov; Tuahuns, Farida; Savitri, Fitri; Yulianto, Fery (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Service Standards in hospitals related to pharmaceuticals are divided into several criteria, one of which is the waiting time for prescription services. Tangerang Regency general hospital is one of the type B government hospitals, being a referral makes RSU Tangerang Regency experience a buildup of patients in each polyclinic which results in many prescriptions entering outpatient pharmacies so that they often experience a buildup of prescriptions that cause discomfort to patients. The purpose of this study was to determine what is the average waiting time for outpatient prescription services at Tangerang Regency General Hospital and the percentage of conformity of non- concoction or concoction prescriptions with prescription service standards in accordance with the ministry of health. This study is a descriptive study using primary data, namely waiting time data recorded directly. Waiting time data obtained from direct observation during prescription services in outpatient pharmacy installations with research instruments using excel computer waiting time, data with a total population of 5087 outpatient prescriptions. The data that has been obtained is then analyzed using the mean formula (average value). The results of the research show that the average service for non-concocted drug prescriptions is more than 30 minutes and the average service for prescriptions of concocted medicines is more than 60 minutes, so that the suitability of waiting times for non-concocted and concocted prescriptions is still greater than that which does not comply with the minimum service standards.